Studi Komparatif Makna Kasb dalam Quran dan Hadits Perspektif Etos Kerja Max Weber - Ahmad Lukman Nugraha; Ahmad Hasan Ridwan (Yayasan Al Ma'arif Dawuhan, 2026)
This paper explores the concept of al-kasb (human effort) in the Qur'an and Hadith, with the aim of analyzing its semantic dimensions and comparing it with Max Weber's theory of work ethic, particularly the notion of a divine